Influence of micro-organisms upon civilization - Sandt, Victor Irvin (My University, 1894)
Introduction: The following article treats micro-organisms in a general way, first as builders, second as scavengers, and third as disease producers.
Citation: Sandt, Victor Irvin. Influence of micro-organisms upon civilization. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Microbiology; Micro-organism; Civilization; Disease; Anthropology; Theses; Manuscripts (documents)